MICROSPORIDIAN Nosema spp. IN HONEY BEE COLONIES: ASSESSMENT OF INCIDENCE, MOLECULAR CHARACTERIZATION, AND ENVIRONMENTAL CORRELATIONS - Shah Alam; Muhammad Asif Aziz; Javaid Iqbal; Imran Bodlah; Gulshan Irshad; Ali Zeshan (Journal of Animal and Plant Sciences, 2025)
Microsporidian parasites, Nosema spp. substantially affect the health of honey bee colonies. The current research provides extensive insights into the seasonal occurrence of Nosemosis in Apis mellifera, molecular identification of Nosema species, and its correlation with environmental factors. Of the two Nosema species (Nosema apis and Nosema ceranae), molecular identification using specific primers (321-APIS for N. apis and 218-MITOC for N. ceranae) confirmed the exclusive presence of N. ceranae in colonies of A. mellifera across three regions of Pakistan. Nosema incidence was categorized in three levels (I: 0-25%, II: 26-50%, and III: 51-75%) with Khyber Pakhtunkhwa (KPK) region showing the highest infection rates ranging from 16.6–75.0%, compared to Punjab (8.3–33.3%) and the Capital Territory (8.3–25.0%). Out of 300 colonies surveyed across all geographical regions, 101 colonies (33.66%) were found to be infected, with the highest prevalence observed in KPK (59.16%), followed by the Capital Territory (CT) at 18.33% and Punjab at 15.83%. Mean spore count per bee was highest in KPK (0.610 million), followed by the Punjab (0.396 million) and CT (0.349 million) regions. Winter, autumn, and spring seasons were conducive for Nosemosis prevalence in KPK (75%, 69.4%, and 49.9%, respectively), and winter, autumn and summer in Punjab (20.8%, 16.6%, and 16.6%, respectively). Summer and autumn in the CT region showed Nosemosis levels of 25.0% and 13.8%, respectively, with no cases reported during winter and spring seasons.Nosemosis showed positive significant correlations with relative humidity (0.78) in winter, and with distance to floral & water sources (0.90) in autumn.Beekeepers nationwide should monitor and manage Nosema infections to minimize colony impact.
Keywords: Honey bee; Apiaries; Nosema ceranae; Nosema apis; Nosemosis; Molecular diagnosis; Spore count; Seasons; Ecology